The Subaltern in the Ibis Trilogy. Issue 1 (16th June 2022) - Sekar, Sindhu
Abstract: Are the stories of the subaltern just as important as those of our national heroes and leaders, who are considered architects of our nation? How does one define the subaltern? What is the Subaltern Studies project? Does the charge of elitism in the historiography of Indian nationalism hold water? How does the Ibis Trilogy by Amitav Ghosh tackle these issues surrounding the subaltern and their representation in our national history? How does he redefine the nation for us through a multidimensional perspective? What are the historical strategies employed by Ghosh, to this end?